Religion as Social Reality - Rota, Andrea (Method & theory in the study of religion, 2016)
In this article I argue that the shift from a private to a public–social understanding of religion raises new ontological and epistemological questions for the scientific study of religion\s. These questions are deeply related to three central features of the emic–etic debate, namely the problems of intentionality, objectivity, and comparison. Focusing on these interrelated issues, I discuss the potential of John Searle’s philosophy of society for the scientific study of religion\s. Considering the role of intentionality at the social level, I present Searle’s concept of “social ontology” and discuss its epistemological implications. To clarify Searle’s position regarding the objectivity of the social sciences, I propose a heuristic model contrasting different stances within the scientific study of religion\s. Finally, I explore some problematic aspects of Searle’s views for a comparative study of religion\s, and sketch a solution within his framework. I shall argue that a distinction between the epistemological and ontological dimensions of religious affairs would help clarify the issues at stake in the past and future of the emic–etic debate.